2019
DOI: 10.3390/ijms20215503
|View full text |Cite
|
Sign up to set email alerts
|

Immune and Inflammatory Cells of the Tumor Microenvironment Represent Novel Therapeutic Targets in Classical Hodgkin Lymphoma

Abstract: Classical Hodgkin Lymphoma (cHL) is a B-cell malignancy that, typically, responds well to standard therapies. However, patients who relapse after standard regimens or are refractory to induction therapy have a dismal outcome. The implementation of novel therapies such as the anti-CD30 monoclonal antibody Brentuximab Vedotin and immune checkpoint inhibitors has provided curative options for many of these patients. Nonetheless, responses are rarely durable, emphasizing the need for new agents. cHL is characteriz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
57
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(63 citation statements)
references
References 134 publications
2
57
0
4
Order By: Relevance
“…regulatory T cells (Tregs) and Tumor associated macrophages (TAMs)). 5 , 6 Their complex interactions within the HL microenvironment have been well summarized and discussed. 5 8 This review will focus on the contribution of trogocytosis, 9 , 10 also called transendocytosis, 11 to the establishment of the immunosuppressive microenvironment in HL.…”
Section: Hodgkin Lymphomamentioning
confidence: 99%
“…regulatory T cells (Tregs) and Tumor associated macrophages (TAMs)). 5 , 6 Their complex interactions within the HL microenvironment have been well summarized and discussed. 5 8 This review will focus on the contribution of trogocytosis, 9 , 10 also called transendocytosis, 11 to the establishment of the immunosuppressive microenvironment in HL.…”
Section: Hodgkin Lymphomamentioning
confidence: 99%
“…Neutrophils are the most well-known marker and promoter of inflammation (9). Recent findings have indicated that inflammation, metabolic response, and immune response are the three main components of tumor microenvironment, which are of significance in cancer pathogenesis and progression by interacting with tumor cells (9)(10)(11)(12)(13). Several chemokines, cytokines and angiogenic factors produced by neutrophils may result in inflammatory cell recruitment and activation that crucially impact the tumor microenvironment, which could facilitate tumor cell proliferation, microvascular regeneration and tumor progression (9,14,15).…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, R/R patients may be biologically more homogeneous, since treatments might result in resistant clones' selection. Moreover, the non-neoplastic cells of tumor microenvironment have been claimed as one of the main determinants responsible for pathogenesis and progression of HL (Mottok & Steidl, 2018;Calabretta et al, 2019). Infiltration of the tumor microenvironment by CD68+ and CD163+ macrophages, Treg and CD4 + T cells (especially with Th2 phenotype), and high CD4/CD8 ratio is associated to the emergence of resistance to conventional therapy, and a worse prognosis.…”
Section: Discussionmentioning
confidence: 99%